(untitled) (Journal of Rangpur Medical College, 2022)
Background: Community clinics (CC) have been restarted in 2009 by the government of Bangladesh through a project called “Revitalization of Community Health Care Initiatives in Bangladesh” (RCHCIB) to accomplish the ambitious project of establishing 18,000 community clinics. Since then 10,723 Community clinics have been established and they provide free health and family planning services to rural people (for every 6000 population one CC). Objective: The study aimed to assess the prevalence of access and utilization of services provided through community clinics by rural people. Methods: This cross-sectional descriptive study was conducted in Palashbari, Gaibandha district from 15th March 2019 to 20th April 2019. 568 respondents were selected conveniently from the catchment area of 6 community clinics (CCs). Data were collected by face-to-face interviews with a pretested structured questionnaire. Results: Among 568 respondents, majority ware in the age group of 31-50 years (45.4%),female (83%) and housewives (76.8%).93.5% of the respondents visited community clinics. And 85.6% were benefited from the community clinic service. Maternal and child health service utilization was poor (pregnancy registration 27.6%, ANC and PNC 45.2%, family planning services 49.3%) and there is no normal delivery service in the community clinic. 66.2% of the respondents availed EPI Services, 45.8% received Health Education, 65.3% received Vitamin-A Supplementation, 59.9% availed Child Care Services, 71.7% received Treatment of Minor Illness and Diseases, 17.4% availed Referral Services. Conclusion: The CCs are well located in terms of access. According to the Respondents’ services provided by the community, the clinic was average. Maternal and child health services, pregnancy, and birth registration were below the mark. There is no normal delivery service and according to the respondent’s opinion referral system was also poor. J Rang Med Col. September 2022; Vol. 7, No. 2:20-24